Environment guard model as dyadic three-person game with the generalized fine for the reservoir pollution - Romanuke, V.V. (Екологічна безпека та природокористування, 2010)
There is investigated the noncooperative dyadic three-person game with the parameter, defining the penalty for the reservoir pollution. Given NE-solutions of this game as the environment guard model not only contain simultaneously symmetrical and favorable NE-situations for the pollution subjects, but also may be used to force these subjects to apply the cleaning installations completely within the non-equilibrant situation, allowing to lose minimally though. Досліджується безкоаліційна діадична гра трьох осіб з параметром, що визначає стягнення за забруднення водойми. Наведені NE-розв.язки цієї гри як моделі охорони довкілля не тільки містять одночасно симетричні та вигідні NE-ситуації для суб.єктів забруднення, але також можуть бути використані для того, щоб змусити ці суб'єкти застосовувати очисні споруди у рамках нерівноважної ситуації, що, втім, дозволяє досягати мінімальних втрат. Исследуется бескоалиционная диадическая игра трёх лиц с параметром, что определяет взыскание за загрязнение водоёма. Приведённые NE-решения этой игры как модели охраны окружающей среды не только содержат одновременно выгодные NE-ситуации для субъектов загрязнения, но также могут быть использованы для того, что- бы вынудить эти субъекты применять очистительные сооружения в рамках неравновесной ситуации, что, впрочем, позволяет достичь минимальных потерь.